2008
DOI: 10.1111/j.1537-2995.2007.01596.x
|View full text |Cite
|
Sign up to set email alerts
|

Rapid detection of anti‐Lub with recombinant Lub protein and the particle gel immunoassay

Abstract: Recombinant blood group proteins may be able to dispense with the need for RBCs for identification of certain RBC alloantibodies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 12 publications
1
15
0
Order By: Relevance
“…Although neither Lu8 on the Lutheran glycoprotein nor WES b on the Cr protein had been tested before, these antigens efficiently neutralized the corresponding antibodies in the inhibition assay used in this study. In general, this study and earlier studies have demonstrated that the tested rBGPs remain stable for 6 months or longer when stored at 2 to 8°C, independent of the specificity and source of the protein 3‐5,8. This also holds true when the proteins are used in highly concentrated cocktails.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…Although neither Lu8 on the Lutheran glycoprotein nor WES b on the Cr protein had been tested before, these antigens efficiently neutralized the corresponding antibodies in the inhibition assay used in this study. In general, this study and earlier studies have demonstrated that the tested rBGPs remain stable for 6 months or longer when stored at 2 to 8°C, independent of the specificity and source of the protein 3‐5,8. This also holds true when the proteins are used in highly concentrated cocktails.…”
Section: Discussionsupporting
confidence: 78%
“…§ Those antigens shown in earlier studies to be correctly expressed and capable of inhibiting antibodies with the corresponding specificities 3‐5,8,10…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recombinant proteins are used for their capacity to inhibiting hemagglutination assay indicating incompatibility reaction or to trap the antibodies or ligands associated with these proteins in ELISA-type testing [20,24,[64][65][66][67].…”
Section: Towards the Creation Of New Diagnostic Toolsmentioning
confidence: 99%